Abdominal adenopathy found during a routine follow-up. Issue 2 (February 2015) - Carmagnola, Stefania; Venezia, Ludovica; Anderloni, Andrea; Nicali, Roberta; Patrucco, Filippo; Balbo, Piero Emilio
Abstract : ABSTRACT: During routine follow-up of a 60-year-old man with an endoluminal lesion of the duodenum, we found a persistent reactive abdominal adenopathy of unknown origin, later diagnosed as an abdominal localization of sarcoidosis. This article focuses on the differential diagnosis of abdominal granulomatous lymphadenopathies, the management of abdominal adenopathy of unknown origin, and the difficult decision making about sampling lymph nodes with reactive and inflammatory echographic appearance.